2014
DOI: 10.1002/2013ja019454
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of core field polarity of magnetotail flux ropes with the IMF By: Reconnection guide field dependency

Abstract: The relationship between the core field and the interplanetary magnetic field (IMF) B y has been addressed by spacecraft observations in the magnetotail, but it is not yet fully clear since observations by Slavin et al. (2003) and Borg et al. (2012) show controversial results. In this study, we examine 13 flux ropes from the Cluster observations to show for the first time that the correlation between the core field B core and the IMF B y depends on the guide field B g . For large guide fields (> 20% of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 32 publications
4
39
2
Order By: Relevance
“…Results from Teh et al . [] are thus different from Lui et al . [] for which the change of the core field polarity occurred within the complex flux rope structure.…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Results from Teh et al . [] are thus different from Lui et al . [] for which the change of the core field polarity occurred within the complex flux rope structure.…”
Section: Introductioncontrasting
confidence: 62%
“…Recently, Teh et al . [] showed that the correlation between the core field polarity of the magnetotail flux ropes and the IMF B y is guide‐field dependent: for strong guide fields (>20% of the reconnecting field), the core field polarity was correlated with the IMF B y , while for weak guide fields (<10% of the reconnecting field) the core fields have either a positive or negative polarity, irrespective of the IMF B y . However, due to the small guide field strength (<2.0 nT) and the dynamic motion of the current sheet, they cannot unambiguously determine whether the polarity of the guide field changed during the event, when considering the uncertainty of the estimate of the X‐line orientation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Grad-Shafranov (GS) (Hau and Sonnerup, 1999;Hu and Sonnerup, 2002;Sonnerup et al, 2006;Möstl et al, 2009;Isavnin et al, 2011;Teh et al, 2014) reconstruction method is applied to recover the two-dimensional magnetic field maps of the events. The technique assumes that the analyzed magnetic structure is in magnetohydrostatic equilibrium ( p = j × B), and is 2 1/2-dimensional, i.e., the structure has translational symmetry along its invariant axis ( ∂ ∂z = 0).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The magnetic island is characterized by a bundle of circular magnetic field lines without a strong core field in the “cross‐tail” direction [ Borg et al ., ; Kiehas et al ., ; Huang et al ., ]; it is typically a signature/product of multipoint reconnection in the magnetotail [ Deng et al ., ; Eastwood et al ., ; Huang et al ., ; Fu et al ., ]. The magnetic island with strong core field may be related to guide‐field reconnection called the flux rope [ Teh et al ., ; Huang et al ., ], while the magnetic island without core field is usually called magnetic island [ Fu et al ., ] or plasmoid [ Zong et al ., ]. In 2‐D [e.g., Markidis et al ., ] and 3‐D [e.g., Daughton et al ., ] simulations, the magnetic‐island (flux‐rope) structures can be well recognized, as well as in spacecraft in situ measurements [ Slavin et al ., ].…”
Section: Introductionmentioning
confidence: 99%